Perilaku Investor Muslim Dalam Bertransaksi Saham di Pasar Modal - Pramita Agustin; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This research aims to know the muslim investor behavior in a stock transaction in capital market. This research used the qualitative approach, using the case study method by basing on the theory of behavioral finance.Data collection using a purposive sampling technique to determine informants amounted to five muslim investors who at least has a two year stock transaction to be interviewed in depth, observed and evaluated the data by performing a triangulation.The results of this research have findings that muslim investor behavior in a stock transaction is divided into two point of view that is, investors who consider religion in their investment decisions and the invetor did not consider religion in their investment decisions. Investors who consider religion in their investment decisions preferring stock composition of the incoming Sharia index list and nature of investments tend to be long term. Investors who do not consider religion in choosing his investment decision stock blends well in the Shariahcompliantindex or not. The nature of investment investors who did not consider the shortterm nature of the religion. REFERENCES Abd. Al-Baqi, Muhammad Fuad. 2010. Kumpulan Hadis Sahih Al-Bukhari Muslim, Terjemahan Arif Rahman Hakim. Solo: Insan Kamil.Alexander, Gordon J dan William Sharpe.1997.Fundamental of Investment. Prentice Hall Inc, Englewood, New Jersey.Al-Qur’an Indonesia.2013. Tanpa Judul.(Online). http://www.alquranindonesia.com/) diakses pada Kamis, 9 Januari 2013, jam 00.52 WIB.Aziz, Abdul. 2010. Manajemen Investsi Syariah. Bandung: Alfabeta. Cetakan Kesatu. Daniel,Kent.1998.”Investor Psychology and Security Market Under and Over. Reaction”. Journal of Asset Finance Vol 53, PP 1839-1886Hayes, Suzanne K. 2010. Exploring Investor Decision in a Behavioral Finance Framework. Journal of Family and Cunsumer Sciences Vol 102. No. 2. Hal: 56-60.Huda, Nurul. Mustafa Edwin. 2007. Investasi pada Pasar Modal Syariah. Jakarta: Kencana. Cetakan Kesatu. Jamaluddin, Ancok dan Fuad NashoriSuroso.1994. Psikologi Islami; Solusi Atas Problem-problem Psikologi. Yogyakarta. Pustaka Pelajar. Kumpulan Fatwa Dewan Syariah Nasional Majelis Ulama Indonesia.Litner, G. 1998. Behavioral Finance: Why Investor Make Bad Decisions. The Planner 13 (1). Hal: 7-8.Manap, dkk..2007.The Principles of Islamic Religiosity and Religious Personality Measurement. Jurnal Akademik: Koleksi Artikel Ilmiah untuk Dikongsi, Dianalisis dan Dibahaskan [On-line series]. http://jurnalakademik.com/2006/0 9/principles-of-islamic-eligiosityNafik Ryandono, Muhamad. 2009. Bursa Efek & Investasi Syariah. Jakarta: Serambi Ilmu Semesta. Cetakan Kesatu.Nagy, Robert dan Obenberger. 1994. Factors Influencing Individual Investors Behaviour. Financial Analysts Journal. hal 63-68.Nofsinger, Jhon R. 2005. Psychologi of Investing. Secon Edition. New Jersey. Precentice-Hall Inc.Puspitaningtyas, Zarah. 2012. Relevansi Nilai Informasi Akuntansi dan Manfaatnya bagi Investor. EKUITAS: Jurnal Ekonomi dan Keuangan Vol. 16. No. 2. Hal: 164-183.Puspitaningtyas, Zarah dan Agung Kurniawan. 2012. Prediksi Tingkat Pengembalian Investasi Berupa Deviden Yield berdasarkan Analisis Finansial Rasio. Majalah Ekonomi: Telaah Manajemen, Akuntansi, dan Bisnis, Vol. 16. No.1. Hal: 89-98.Puspitaningtyas, Zarah. 2013. Perilaku Investor dalam Pengambilan Keputusan Investasi. (Diakses dari www.researchgate.com pada Senin, 26 Januari 2014, pukul 19.48)Ricciardi, V dan Simon. 2000. What is Behaviour in Finance?. Business, Education,and Technology Journal. Fall. Hal:1-9.Ritter, Jay R. 2003. “Behavioral Finance”. Pasific-Basin Finance Journal Vol 11, pp 429-437.Roth, Allan S. 2007. Behavioral Finance. Article Wealth Logic, LLC.Shahzad, Syed J.H. dkk. 2013. Stock Market Efficiency: Behavioral or Traditional Paradigm? Evidence From Kawachi Stock Exchange and Investor Community of Pakistan. Interdisciplinary Journal of Contemporary Research In Business Vol. 4. No. 10. Hal: 605-619.Sunariyah. 2000. Pengantar Pengetahuan Pasar Modal. Yogyakarta: Unit Penerbit dan Percetakan Akademi Manajemen Preusan YKPN.Sutedi, Adrian. 2011. Pasar Modal Syariah. Jakarta: Sinar Grafika. Cetakan Kesatu.Tandelilin, Eduardus. 2010. Portofolio dan Investasi. Yogyakarta: BPFE Tilson, Whitney. 2005. Applying Behavioral Finance to Value Investing. Artikel Partner LLC.com